1984
DOI: 10.1056/nejm198408233110805
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Status in Chronic Illness

Abstract: Assumptions that psychological attributes are specific to particular diagnoses characterize many investigations of chronically ill patients. We studied 758 patients, each of whom had one of six different chronic illnesses, to determine and compare their scores on the Mental Health Index. Five groups of physically ill patients (with arthritis, diabetes, cancer, renal disease, or dermatologic disorders) did not differ significantly from one another or from the general public, but all had significantly higher sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(79 citation statements)
references
References 37 publications
4
68
1
3
Order By: Relevance
“…Empirical studies have shown that, despite the incurability, treatment regimes, and reality of disability accompanying most chronic conditions, most patients adapt to a chronic disease. For example, Cassileth et al (1984) have shown that most outpatients with diabetes, cancer, and rheumatic, renal, and skin diseases do not report higher levels of stress and lower levels of well-being throughout the history of their disease in comparison to comparable healthy subjects, the exceptions being the initial-and end-stages of a disease. The population in this study generally scored rather low on the stressors assessed, indicating that they view their illness as not being very serious.…”
Section: Perceptions Of Patients and Gps Comparedmentioning
confidence: 99%
“…Empirical studies have shown that, despite the incurability, treatment regimes, and reality of disability accompanying most chronic conditions, most patients adapt to a chronic disease. For example, Cassileth et al (1984) have shown that most outpatients with diabetes, cancer, and rheumatic, renal, and skin diseases do not report higher levels of stress and lower levels of well-being throughout the history of their disease in comparison to comparable healthy subjects, the exceptions being the initial-and end-stages of a disease. The population in this study generally scored rather low on the stressors assessed, indicating that they view their illness as not being very serious.…”
Section: Perceptions Of Patients and Gps Comparedmentioning
confidence: 99%
“…A higher score is indicative of greater psychological distress. The MHI is a valid and reliable measure of mental health that has been used extensively in both clinical and nonclinical samples (Cassileth et al, 1984;Heubeck & Neill, 2000;Rosenthal et al, 1991;Veit & Ware, 1983). It was also used previously to examine the impact of stigma on psychological distress (Stutterheim et al, 2009;Stutterheim et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In the initial phase of an illness life events are often considered as part of the illness ('the umbrella of illness') while in the chronic phase of illness life events are ne glected [24], Side effects are in this phase of illness often confounded with life events.…”
Section: Somatic Dimension: Side Effects O F Treatmentmentioning
confidence: 99%
“…Else where, it has been shown that the General Health Questionnaire also, and perhaps to a larger extent, covers these elements [22], In minor somatic disorders (e.g. neuras thenia [23]) and in major somatic disorders [24] the Beck Depression Inventory (BDI) has been found useful as an indicator of cop ing with illness. The BDI correlated signifi cantly with the General Well-Being Schedule as an index of mental health [24], In mental disorders, however, such ques tionnaires as GIIQ or BDI are problematic.…”
Section: The Psychological Dimensionmentioning
confidence: 99%
See 1 more Smart Citation